2014
DOI: 10.1039/c4ob01387e
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective synthesis of C-fused pyranoindoles, pyranobenzofurans and pyranobenzothiophene scaffolds using oxa-Pictet–Spengler type reaction of vinylogous carbonates

Abstract: C-fused pyranoheterocycles can be readily assembled using an intramolecular oxa-Pictet-Spengler type reaction of vinylogous carbonates in a highly stereoselective manner. Required indole and benzofuran rings tethered to vinylogous carbonates are prepared by a tandem Sonogashira coupling-nucleopalladation reaction. The entire process can also be carried out in a 'one-pot' manner starting from homopropargyl alcohol. The C-fused pyranoindoles could be converted to spirooxindoles as well as to ring expanded produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…All chemicals were used and purchased from Sigma-Aldrich without puri cation unless otherwise commented. The products were characterized by NMR data that were acquired for 1 H at 500 MHz and for 13 Then, 0.6 mL solution of NH4Cl were added drop by drop to the mixture within 1-2 min. After that, 0.1 mmol Zn powder was added and stirred for 3 h. The progress of reaction was monitored by Thin Layer Chromatography (TLC) using n-hexane/ethyl acetate (1:5) as eluent.…”
Section: General Informationmentioning
confidence: 99%
“…All chemicals were used and purchased from Sigma-Aldrich without puri cation unless otherwise commented. The products were characterized by NMR data that were acquired for 1 H at 500 MHz and for 13 Then, 0.6 mL solution of NH4Cl were added drop by drop to the mixture within 1-2 min. After that, 0.1 mmol Zn powder was added and stirred for 3 h. The progress of reaction was monitored by Thin Layer Chromatography (TLC) using n-hexane/ethyl acetate (1:5) as eluent.…”
Section: General Informationmentioning
confidence: 99%
“…Gharpure and Prasath explored the oxa-Pictet-Spengler type reaction of vinylogous carbonates for the stereoselective synthesis of tetrahydropyrano [3,4b]indoles (series 4) [77]. Xie et al reported the Rh(II)catalyzed intramolecular annulation of N-sulfonyl-1,2,3-triazoles towards the highly stereoselective synthesis of series 4 pyranoindoles (Scheme 13) [78].…”
Section: Chiral Hydropyrano[23-b]indoles and Hydropyrano[32-b]indolesmentioning
confidence: 99%
“…Among the products, pyrano-pyrazole 12 and indolo-pyran frameworks 13 show a wide variety of pharmaceutical activities; some important scaffolds with the pyrano-benzofuran moiety 14 are also known. Selected examples of pharmaceutically relevant fused-pyrans are depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%